Poesia cênica. A arte do ator no Teatro Épico-Dialético - Prado Zavala, Jaime Jorge (2021)
This monographic case report seeks to make Bertholt Brecht's theatrical poetics known to those who do not know, and offer other perspectives to those who have already approached. Based on Massimo Castri, Bertholt Brecht, Luis de Tavira and the experience of some theatrical interpreters, the characteristics of the acting profile of epic-dialectical theater are analyzed and, from that perspective, the particular work of the National Theater Company (Mexico) in his staging of The Circle of Lime. This is how the work seeks to explain this theatricality to those who are not familiar with Brecht's theater and also to open other perspectives to its connoisseurs.